Assessment of Outcome of Arthroscopic Subtotal Coronoidectomy in Treating Medial Coronoid Disease and Effect of Concurrent Autologous Conditioned Plasma in Dogs Using Force Plate Analysis - Scharpf, Marlene; Theyse, Lars F.H. (Veterinary and Comparative Orthopaedics and Traumatology, 2023)
Objective The aim of this study was to assess the outcome of arthroscopic subtotal coronoidectomy in treating medial coronoid disease and the effect of concurrent autologous conditioned plasma (ACP) in dogs using force plate analysis.Study Design This study included 16 dogs with unilateral medial coronoid disease based on computed tomographic imaging. Treatment consisted of an arthroscopic subtotal coronoidectomy. As concurrent therapy, eight dogs received ACP at the end of the arthroscopy and eight dogs a placebo. Force plate analysis, including vertical forces, braking and propulsive forces, corresponding impulses and symmetry indices, was performed prior to arthroscopy and at 4, 12 and 26 weeks postoperatively.Results After an initial reduction of all force plate analysis parameters, vertical and propulsive parameters gradually improved to the level of healthy dogs at 26 weeks postoperatively. In contrast, braking parameters did not reach normal values at 26 weeks, demonstrating ongoing loss of elbow joint function. The ACP and placebo group did not show any significant difference in force plate analysis parameters during the 26 weeks study period.Conclusion Arthroscopic subtotal coronoidectomy did not result in complete normalization of ground reaction forces, impulses and symmetry indices. Concurrent treatment with ACP, immediately after arthroscopy, did not improve outcome. Our results show that outcome of arthroscopic subtotal coronoidectomy in treating medial coronoid disease is less favourable than previously reported.
Keywords: medial coronoid disease; arthroscopy; subtotal coronoidectomy; autologous conditioned plasma; force plate analysis